Constitutionalization of the Right to Abortion from Different Understandings of Autonomy - Ana Micaela Alterio (Athena, 2025)
This article explores the constitutionalization of abortion in Mexico within the broader framework of Latin American constitutionalism. It highlights the pivotal institutional reforms of 1994 and 2011 that redefined the role of the Mexican Supreme Court and elevated international human rights instruments to constitutional status. These reforms opened new legal avenues for feminist advocacy, enabling the recognition of reproductive rights. The article conceptualizes three jurisprudential approaches to abortion: (1) unjustified paternalism, often manifest under causal regulatory frameworks; (2) a negative liberal theory of autonomy, characteristic of decriminalization arguments; and (3) relational autonomy, which emphasizes contextual and substantive equality considerations. By examining key Supreme Court cases, the author identifies a progressive shift toward recognizing abortion as a fundamental right, which allows for the construction of reasons in favour of a narrative based on the relational conception of autonomy and substantive equality. The article aims to contribute to feminist legal strategies by clarifying the argumentative frameworks surrounding reproductive autonomy in constitutional adjudication.